Analisis Efektifitas dan Kontribusi Pendapatan Asli Daerah (PAD) Kota Banda Aceh - Dahlia Dahlia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2018)
This study aims to determine the effectiveness of the collection of sources of Regional Original Revenue (PAD), namely local taxes, regional levies, regional company profits, and other legitimate income managed by the Banda Aceh City Revenue Service. At the same time, it also analyzes whether local taxes, regional levies, regional company profits, and other legitimate income contribute to increasing PAD in Banda Aceh. Data analysis used in this study is effectiveness ratio analysis and contribution analysis. For the purposes of analysis, secondary data is used for the period 2007-2011. The results of this study reveal that, on average, the level of effectiveness is in the very effective category for local taxes, effective for regional retribution, less effective for regional company profits, and very effective for other legitimate income. While for analyzing contributions, on average the level of contribution of local taxes, regional retribution, regional company profits, and other legitimate income is in the category of good for local taxes, moderate for regional retribution, very less for regional company profits, and medium for other legitimate income.